A Pilot Study of Medical Misinformation Perceptions and Training Among Practitioners in North Carolina (USA). (11th August 2021) - Wood, Jamie L.; Lee, Grace Y.; Stinnett, Sandra S.; Southwell, Brian G.
Medical misinformation (MM) is a problem for both medical practitioners and patients in the 21 st century. Medical practitioners have anecdotally reported encounters with patient-held misinformation, but to date we lack evidence that quantifies this phenomenon. We surveyed licensed practitioners in the state of North Carolina to better understand how often patients mention MM in the clinical setting, and if medical practitioners are trained to engage with patients in these specific conversations. We administered an anonymous, online survey to physicians and physician assistants licensed to practice in the state of North Carolina. Questions focused on demographics, clinical encounters with MM, and training to discuss MM with patients. We received over 2800 responses and analyzed 2183 after removing ineligible responses. Our results showed that most respondents encountered MM from patients (94.2% (2047/2183)), with no significant differences between clinical specialty, time spent in practice, or community type. When asked about specific training, 18% (380/2081) reported formal experiences and 39% (807/289) reported informal experiences. MM has been salient due to the COVID-19 pandemic; however, it was present before and will remain after the pandemic. Given that MM is widespread but practitioners lack training on engaging patients in these conversations, a sustained effort to specifically train current and future practitioners on how to engage patients about MM would be an important step toward mitigating the spread of MM.